Surgical and short-term outcomes in robotic and laparoscopic distal gastrectomy for gastric cancer with enhanced recovery after surgery protocol: A propensity score matching analysis - Huang, Weijia; Liu, Siyu; Chen, Junqiang (Frontiers in Surgery, 2022)
Abstract Objective:To evaluate the short-term surgical outcomes of laparoscopy-assisted distal gastrectomy (LADG) and robot-assisted distal gastrectomy (RADG) for gastric cancer (GC) with enhanced recovery after surgery (ERAS) protocol. Methods: We reviewed the medical records of 202 patients undergoing radical distal gastrectomy; among them, 67 cases were assisted through RADG, while 135 cases were assisted through LADG along with ERAS. We retrospectively collected in succession from a database (January 2016–March 2019). We adopted propensity score matching (PSM) to compare surgical and short-term outcomes of both groups. Results: After the successful examination of 134 cases, including 67 receiving RADG and 67 undergoing LADG, the operative times were noted as 5.78 ±0.96 h for the RADG group and 4.47 ±1.01 h for the LADG group (P＜0.001). The blood loss was noted as 125.52 ±101.18 ml in the RADG group and 164.93 ±109.32 ml in the LADG group (P＜0.05). The shorter time to first flatus was 38.82 ±10.56 h in the RADG group, and 42.88 ±11.25 h was in the LADG group (P＜0.05 ). While shorter days of postoperative hospital stay 5.94 ±1.89 d in the RADG group and 6.64 ±1.92 d in the LADG group ( P＜0.05 ). Also, the RADG group (84483.03 ±9487.37) was much more costly than the LADG group (65258.13 ±8928.33) (P＜0.001). The postoperative overall complication rates, numbers of dissected lymph nodes, visual analog scale (VAS), time to start liquid diet for RADG group as well as for LADG group were similar. Conclusions: In this research, we concluded that RADG provides surgical benefits and short-term outcomes as compared to LADG for GC with the ERAS.